Ser trabalhador na cidade : relações de classe em Uberlândia : fins do século XX e início do século XXI - Santos, Carlos Meneses de Sousa (2009)
This work tried to discuss what means to be workers in the city of Uberlândia- MG, in the end of the century XX and beginning of the century XXI. For so much, I left of workers' experiences with the intention of to realize like them are elaborated in the confrontation of values and interests. I made the road of penetrating in the field of the relationships, contradictory and conflicting, in that the condition of the workers' class appears as common territory, expressing their life manners and impelling the production of fields of dispute possibilities, for their needs and expectations. With that interest, the selected sources were understood as established dialogues by certain workers in certain relationships produced along these last 30 years. In those documents I tried to realize the social experience of the subjects that were involved in the production of those relationships, looking for to observe as that performance marks his social conscience. That procedure was possible for taking that dynamics as of classes. Therefore, the theoretical and politician basis is it of class, this understood as constituent process in the social relationships, as territory of the relationship of power maintained in the city, therefore, of the own fight of classes in the capitalist society. The proposal was to evidence the practices of social participation undertaken by workers to the live the city, trying to realize which city projects were and are in subject. In that plot, Uberlândia is presented as the expression of the relationship of protagonisms, entrenched in the inequality of conditions and in the different present alternatives in the relationships of classes. That direction put in focus the identifications and dissidences that are built in the defense of certain interests, as well as in the face up of other. I intended to detach the complete and complex men's potency to the they try the total universe of their relationships, recognizing that the same subjects face up varied questions and pressures that challenge and fasten limits to their life manners, practices that move doing of the relationships of classes, evidencing a historical process in construction. That route went affirming the perception that the contradictions and the tension compose the social relationships and, mainly, it problematized the way as workers rights experience the life as workers in the city.